Cybercrime and cloud forensics : applications for investigation processes - Ruan, Keyun, 1986- (Hershey, PA : Information Science Reference, 2013)
"This book presents a collection of research and case studies of applications for investigation processes in cloud computing environments, offering perspectives of cloud customers, security architects as well as law enforcement agencies on the new area of cloud forensics"--
Includes bibliographical references (pages 345-368) and index.
Keywords: Computer crimes -- Investigation; Forensic sciences -- Data processing; Cloud computing; Computer crimes -- Investigation -- Case studies; Cloud computing -- Case studies